Modulators of HIF1α and NFkB in Cancer Treatment: Is it a Rational Approach for Controlling Malignant Progression? - Tafani, Marco; Pucci, Bruna; Russo, Andrea; Schito, Luana; Pellegrini, Laura; Perrone, Giulietta A.; Villanova, Lidia; Salvatori, Luisa; Ravenna, Linda; Petrangeli, Elisa; Russo, Matteo A. (Frontiers in Pharmacology, 2013)
HIF1 and NFkB are two transcription factors very frequently activated in tumors and involved in tumor growth, progression and resistance to chemotherapy. In fact, HIF1 and NFkB together regulate transcription of over a thousand genes that, in turn, control vital cellular processes such as adaptation to the hypoxia, metabolic reprogramming, inflammatory-reparative response, extracellular matrix digestion, migration and invasion, adhesion, etc. Because of this wide involvement they could control in an integrated manner the origin of the malignant phenotype. Interestingly, hypoxia and inflammation have been sequentially bridged in tumors by the discovery that alarmin receptors genes such as RAGE, P2X7 and some TLRs, are activated by HIF1; and that, in turn, alarmin receptors strongly activate NFkB and proinflammatory gene expression, evidencing all the hallmarks of the malignant phenotype. Recently, a large number of drugs have been identified that inhibit one or both transcription factors with promising results in terms of controlling tumor progression. In addition, many of these molecules are natural compounds or off-label drugs already used to cure other pathologies. Some of them are undergoing clinical trials and soon they will be used alone or in combination with standard anti-tumoral agents to achieve a better treatment of tumors with reduction of metastasis formation and, more importantly, with a net increase in survival. This review highlights the central role of HIF1 activated in hypoxic regions of the tumor, of NFkB activation and proinflammatory gene expression in transformed cells to understand their progression toward malignancy. Different molecules and strategies to inhibit these transcription factors will be reviewed. Finally, the central role of a new class of deacetylases called Sirtuins in regulating HIF1 and NFkB activity will be outlined.